Consumer Responses to Price Disclosure in Direct-to-Consumer Pharmaceutical Advertising - Garrett, Jace B. (JAMA Intern Med, 2019)
This survey-based behavioral experiment was conducted to understand how consumers are likely to respond to including the drug price in any direct-to-consumer pharmaceutical advertising.